β-Peptides as inhibitors of protein–protein interactions - Kritzer, Joshua A. (2005)
We became interested several years ago in exploring whether 14-helical β-peptide foldamers could bind protein surfaces and inhibit protein–protein interactions, and if so, whether their affinities and specificities would compare favorably with those of natural or miniature proteins. This exploration was complicated initially by the absence of a suitable β-peptide scaffold, one that possessed a well-defined 14-helical structure in water and tolerated the diverse sequence variation required to generate high-affinity protein surface ligands. In this perspective, we describe our approach to the design of adaptable β-peptide scaffolds with high levels of 14-helix structure in water, track the subsequent development of 14-helical β-peptide protein–protein interaction inhibitors, and examine the potential of this strategy for targeting other therapeutically important proteins.